SMART ENERGY MANAGEMENT SYSTEM FOR HIGH-CONSUMPTION HOUSEHOLDS USING RASPBERRY PI AND HYBRID INVERTER - Abdumalikov , Akmaljon; Sherbaev , Javokhir (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This paper introduces the design and implementation of a hardware-based smart energy management system which is designed for high load residential houses with solar panels, battery storage, and hybrid inverter. Using a Raspberry Pi microcomputer the system monitors household consumption and electricity prices in real time, automatically switching from solar battery power in peak periods to grid power when tariffs are lower. The hybrid inverter makes it possible to export excess power to the grid, while also supplying emergency power in the event of grid failure. The system is made up of voltage and current sensors, relay control modules, and a backend service which gathers and retrieves peak hour tariff data. Simulation results confirm that electricity cost can be significantly decreased and the system efficiency can be advanced.